Papel da formação de espécies reativas de oxigênio na apoptose de eosinófilos in vivo: importância para resolução da resposta inflamatória associada à pleurisia e à asma induzida em camundongos - Alesandra Corte Reis (2012)
Eosinophils are effector cells that play an important role in the pathophysiology of allergic disease. In allergic diseases, such as asthma, eosinophils are a crucial source of cytotoxic proteins, lipid mediators, oxygen metabolites, and cytokines, which may contribute to the severity of disease. The accumulation of eosinophil in tissue depends not only on the number of cells being recruited at any particular time, but also on the number of cells that are cleared or leave the tissue. Thus, defective removal of these cells plays an important role in the initiation and propagation of chronic inflammatory diseases. Here we investigated the role of ROS in the resolution of the inflammatory response after induction of asthma and allergic pleurisy in mice. Previous studies have demonstrated the role of ROS as pro-inflammatory mediators but the role of ROS in the resolution phase is poorly understood. For induction of the inflammatory response to ovalbumin adjuvant aluminum hydroxide in mice previously sensitized with the same antigen. There was an initial accumulation of neutrophils at 12 hours and an increase of eosinophils after 24 hours of pleurisy and asthma induction. The resolution of the eosinophilic inflammatory response was initiated with 48 hours and was substantially resolved after 72 hours of antigenic challenge. Administration of H2O2 or SOD resolved eosinophilic inflammation. In addition, the resolution of inflammation induced by SOD or H2O2 was accompanied by an increase in the number of apoptotic eosinophils. Furthermore, eosinophil resolution was delayed in gp91phox-/- mice but not in iNOS-/- mice. Interestingly, ROS production was diminished in gp91phox-/- mice. Moreover, the inhibition of ROS production by apocinin prolonged inflammatory response in asthma model. Our findings indicate that levels of H2O2 increase during eosinophil influx and are necessary for the resolution of allergic inflammation in vivo by induce apoptosis of eosinophils. These results may be relevant as future therapeutic strategies for the treatment of inflammatory diseases that may to become chronic due to lack of resolution.